THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING STUDENTS’ MATHEMATICAL COGNITIVE ABILITIES: A LITERATURE REVIEW - Shofa, Gharitza Zahira; Aziz, Tian Abdul; Hakim, Lukman El (Universitas Sembilanbelas November Kolaka, 2025)
Artificial Intelligence (AI) in education is not only used to provide personalized feedback, but can also be used to build learning systems that can adapt and be tailored to the needs of each student. This study aims to determine the role of AI in improving mathematical cognitive abilities in students. The method used to obtain data is a Systematic Literature Review. Articles were collected using article search engines such as Google Scholar, Science Direct, DOAJ, and Eric. The results of the article search were screened based on predetermined criteria. The final screening resulted in 10 articles from national and international journals being used as literature review material. Based on the analysis, AI has been used at the elementary, junior high, high school, and university levels to improve various mathematical cognitive abilities. The role of AI in mathematical cognitive abilities includes analyzing, evaluating, organizing, and providing space for discussion and reflection. AI plays a role in cognitive abilities such as creative thinking, critical thinking, problem solving, and computational abilities.